Spontaneous bone regeneration achieved through one-step alignment of human mesenchymal stem cell-embedded collagen - Heo,Cheol Ho; Yeo, Ki Baek; Chae, Minjung; Bak, Seon Young; Choi, Hyeon Jin; Jeong, Sohyeon; Choi, Nakwon; Kang, Seung-Kyun; Jun, Sang Ho; Ok, Myoung Ryul; Kim, So Yeon (Elsevier BV, 2025)
Optimizing cell-matrix interactions for effective bone regeneration remains a significant hurdle in tissue engineering. This study presents a novel approach by developing a human mesenchymal stem cells (hMSCs)-embedded 3D aligned collagen for enhanced bone regeneration. A one-step mechanical strain was applied to a mixture of hMSCs and collagen, producing an hMSC-embedded, aligned 3D collagen hydrogel patch that mimics the natural bone matrix. Notably, the hMSCs embedded in the aligned collagen spontaneously differentiated into osteoblasts without external inducing reagents. Immunofluorescence analysis revealed that the BMP2-smad1/5 signaling pathway, critical for osteogenic differentiation, were activated by aligned collagen. In vivo experiments using a calvarial defect model confirmed that this approach effectively promotes new bone formation, starting centrally within the defect rather than from the edges adjacent to the existing bone. Our findings suggest that this simple method of pre-straining to create aligned 3D collagen embedded with hMSCs holds promise as a novel cell therapy platform for bone regeneration.